The Relationship Between the Frequency of Use of Non-Medication Coping Strategies With Urinary Incontinence and Depression in Older Adults - Yildirim, Ozge Oz; Iseri, Ozge (Wiley, 2024)
Background: The aim of this study is to examine the relationship between the frequency of use of non-medication coping strategies with urinary incontinence (UI) and depression in older adults. Methods: This study followed a descriptive design and was conducted with 345 older adults over the age of 65. The data of the study were collected using the Geriatric Depression Scale Short Form and the Frequency of Non-Medication Coping Strategies with Urinary Incontinence Scale. The data analysis of the study was conducted using descriptive statistics, Pearson correlation analysis, and hierarchical multiple regression analysis. The significance level was accepted as P < 0.05. Results: The mean age of the participants was 71.86 +/- 5.43 years. Among the older adults, 58.8% were male and 50.2% were primary school graduates. It was determined that 43.8% of the participants experienced the frequency of UI more than once a week, 36.2% experienced stress incontinence, 51.9% consulted a physician due to UI, 53.6% received treatment for UI, and 47.8% reported that UI had an impact on their social life. The relationship between the frequency of use of non-medication coping strategies with UI and geriatric depression (beta = -0.017; P = 0.043) was found to be significant and negative. It was found that there was a significant and positive relationship between age, frequency of UI, type of UI, the impact of UI on social life, and geriatric depression (P < 0.05). Conclusion and Suggestions: The older adults in this study were found to have moderate depression. It was determined that the level of depression was higher in the older adults who experienced UI more than once a week, those who experienced stress UI, those whose social lives were impacted, and those who had a higher frequency of non-medication coping strategies.
Öz Yildirim, Özge/0000-0003-4810-563X
Keywords: Coping Strategies; Depression; Geriatric; Older Adults; Urinary Incontinence